A glass sensor and a method for preparing the same

By using magnetic control sputtering, light -carved glue exposure, etching, and screen printing laser technology during the preparation of glass Sensor, it solves the problems of scratching, foreign matter, and disconnection of the glass Sensor in the process, which improves the quality of the process and the quality of the process and the yield and the disconnection of the process. Reduce production costs.

CN114741006BActive Publication Date: 2025-01-28牧东光电科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210286288.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-23
Publication Date
2025-01-28
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

During the process, glass sensor often experiences appearance and functional problems such as scratches, foreign objects, broken wires, and impure etching, resulting in a low process yield and increasing production costs.

Method used

Adopt a glass Sensor preparation method, including using weak alkaline or neutral cleaning agent to clean the glass surface. Through the magnetic sputtering process coating ITO, adjust the thickness of the ITO coating to control the obstacles of the control party, and use photoresia and etching solution for precision exposure Etochtate, protect the ITO layer is not damaged, and prepare the edge of the silver slurry through the screen printing and laser technology.

Benefits of technology

Effectively improved the appearance and electrical rate of glass Sensor. The appearance rate increased from 80 % to 90 %, and the electrical yield was increased from 90 % to 95 %. At the same time, the process process and production cost were reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114741006B_ABST
    Figure CN114741006B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a glass sensor, the key technology of which is to protect the glass surface B while etching the glass surface A, and to protect the glass surface A while etching the glass surface B, so as to prevent the glass sensor from having scratches, foreign matter and other poor appearance during the manufacturing process. The conventional Mo‑Al‑Mo conductive material is replaced with a silver paste conductive material to solve functional problems such as edge wiring breakage and incomplete etching. The appearance yield is increased from 80% to 90%, and the electrical yield is increased from 90% to 95%. The present invention also provides a glass sensor, which is obtained by the above process. The present invention adopts a printed silver paste process, and does not require etching. Only baking and laser can obtain the required edge wiring, reduce the process steps, reduce the loss of manpower and material resources, and reduce production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of touch screens, and in particular to a glass sensor and a preparation method thereof. Background Art

[0002] In the automotive and industrial control fields, a large part of touch screens still use glass sensors as the functional layer structure to ensure better safety and higher strength. The glass sensor process yield is generally low, about 70% to 80%, and often has appearance and functional problems such as scratches, foreign matter, broken wires, and unclean etching, resulting in loss of manpower and material resources and increasing production costs. Summary of the invention

[0003] The purpose of the present invention is to provide a glass sensor preparation method to solve the appearance and functional problems such as scratches, foreign matter, broken wires, and unclean etching in the glass sensor manufacturing process, improve the process yield, reduce the loss of manpower and material resources, and reduce production costs.

[0004] In order to solve the above technical problems, a method for preparing a glass sensor of the present invention comprises the following steps:

[0005] Step S1: Use a weak alkaline or neutral cleaning agent to clean the front and back of the glass;

[0006] Step S2: coating ITO on the front and back of the glass by magnetron sputtering, and controlling the thickness of the ITO coating by adjusting the magnetron sputtering conditions to obtain the ITO glass with the required square resistance;

[0007] Step S3: coating photoresist on the A surface of the ITO glass, and then baking at 60° C. to 120° C. for 10 min to 30 min;

[0008] Step S4: Expose the ITO glass coated with photoresist in the designed A-surface glass mask precision exposure machine, develop it in a developer prepared with 90% solid electronic grade KOH to develop the pattern in the A-surface, and then wash it with water and air dry it to dry the liquid on the surface of the ITO glass;

[0009] Step S5: turning over the ITO glass, coating the entire surface of the B surface of the ITO glass with a photoresist of 1 μm to 5 μm, and baking at 60° C. to 120° C. for 10 min to 30 min to form a photoresist film, thereby protecting the ITO on the B surface;

[0010] Step S6: Place the A surface of the ITO glass in an etching solution for etching, remove the ITO that is not needed for the pattern on the surface, and leave the ITO that is needed for the pattern on the surface. Since the B surface is protected by photoresist, the ITO on the B surface will not be affected when the A surface is etched. After washing with water and air drying, the photoresist is stripped and removed in a stripping solution prepared with 99% electronic grade NaOH. After washing with water and air drying, the ITO glass with the pattern on the surface is obtained.

[0011] Step S7: coating photoresist on the ITO glass surface B, and then baking at 60° C. to 120° C. for 10 min to 30 min;

[0012] Step S8: Expose the ITO glass coated with photoresist in the designed B-side glass mask precision exposure machine, develop it in a developer prepared with 90% solid electronic grade KOH to develop the pattern in the B-side, and then dry the liquid on the surface of the ITO glass after washing with water and air drying;

[0013] Step S9: turning over the ITO glass, coating the entire surface of the A surface of the ITO glass with a photoresist of 1 μm to 5 μm, and baking at 60° C. to 120° C. for 10 min to 30 min to form a photoresist film, thereby protecting the ITO on the A surface;

[0014] Step S10: Place the B surface of the ITO glass in an etching solution for etching, remove the ITO that is not needed for the pattern in the surface, and leave the ITO that is needed for the pattern in the surface. Since the A surface is protected by the photoresist, the ITO Pattern on the A surface will not be affected when the B surface is etched. After washing with water and air drying, the photoresist is stripped and removed in a stripping solution prepared with 99% electronic grade NaOH. After washing with water and air drying, the ITO glass with the pattern in the bottom is obtained.

[0015] Step S11: Printing a peelable adhesive on the surface of the ITO pattern on the A side by screen printing technology, and baking it at 120° C. to 150° C. for 10 min to 30 min to form an upper peelable adhesive with viscosity; then printing a peelable adhesive on the surface of the ITO pattern on the B side by screen printing technology, and baking it at 120° C. to 150° C. for 10 min to 30 min to form a lower peelable adhesive with viscosity;

[0016] Step S12: printing silver paste on the edge of the ITO pattern on the A side by screen printing technology, baking at 120°C to 140°C for 10min to 30min to form a block silver paste with thickness, and then lasering a circuit with line width and line spacing by a high-precision laser machine to obtain the upper edge routing; then printing silver paste on the edge of the ITO Pattern on the B side by screen printing technology, baking at 120°C to 140°C for 10min to 30min to form a block silver paste with thickness, and then lasering a circuit with line width and line spacing by a high-precision laser machine to obtain the lower edge routing;

[0017] Step S13: Print the peelable glue on the A side by screen printing technology, and bake it at 120℃~150℃ for 10min~30min to form a thick upper peelable glue; then print the peelable glue on the B side by screen printing technology, and bake it at 120℃~150℃ for 10min~30min to form a thick lower peelable glue.

[0018] Furthermore, the glass is reinforced sodium-lime glass or aluminosilicate glass, with a reinforcement stress of more than 400MPa, a reinforcement depth of 8 to 15μm, and a glass thickness of 0.2mm to 1.1mm. The reinforcement stress of Asahi Glass sodium-lime glass is between 400MPa and 650MPa, and the reinforcement stress of Longwei, Corning and other aluminosilicate glass is more than 700MPa.

[0019] Furthermore, in step S2, the thickness of the ITO coating is 20nm to 60nm, and the square resistance is 30Ω / □ to 100Ω / □. The thicker the ITO thickness, the lower the ITO square resistance. When the ITO thickness is 20nm, the ITO square resistance is 100Ω; when the ITO thickness is 30nm, the ITO square resistance is 60Ω; when the ITO thickness is 60nm, the ITO square resistance is 30Ω.

[0020] Furthermore, in the steps S3 and S7, the coating thickness of the photoresist is 1 μm to 5 μm.

[0021] Furthermore, the etching solution in step S6 and step S10 is aqua regia or FeCl3 prepared by 36% electronic grade HCl and 5% to 68% electronic grade HNO3.

[0022] Furthermore, in step S12 , the thickness of the silver paste is 5 μm to 9 μm, and the line width and line spacing are 10 μm / 10 μm to 40 μm / 40 μm.

[0023] Furthermore, the thickness of the upper peelable adhesive and the lower peelable adhesive in step S13 is 50 μm. The upper peelable adhesive and the lower peelable adhesive are a single-component solvent-based viscous liquid with good adhesive properties and mechanical properties, and can play the role of water resistance, oil resistance, acid resistance, alkali resistance, corrosion resistance, etc., and form a peelable film after curing. The color can be black or blue.

[0024] The present invention also provides a glass sensor, which is manufactured through the above process and includes a peelable adhesive, an upper inner pattern, an upper edge routing, glass, a lower inner pattern, a lower edge routing and a lower peelable adhesive. The upper edge routing and the lower edge routing are silver paste block routings printed on the edge of the in-plane pattern using CCD precision screen printing technology. After the silver paste is baked and solidified, a silver paste circuit is laser-printed by a CCD precision laser machine. The silver paste circuit is connected to the in-plane pattern channel. The upper inner pattern and the upper edge routing constitute a capacitive sensing layer, and the lower inner pattern and the lower edge routing constitute a capacitive driving layer. The capacitive sensing layer and the capacitive driving layer complete the functions of signal reception and transmission.

[0025] Furthermore, the main component of the strippable adhesive is polyvinyl chloride or a vinyl resin derivative, and the main component of the photoresist is a photosensitive resin such as propylene glycol methyl ether acetate, including components such as solvents, resins, photoinitiators and additives.

[0026] The upper inner pattern and the lower inner pattern are a layer of patterned ITO coated on the front and back of the glass. A layer of ITO is first coated on the glass surface by magnetron sputtering, and then the required ITO pattern is obtained by exposure, development, and etching. The pattern of the ITO pattern can be a diamond, a rectangle, a square, or other regular shapes.

[0027] Conventional glass sensors use Mo-Al-Mo as the conductive material for edge routing, and the minimum line width and line spacing is only 20um / 20um. Since the concentration of Mo-Al-Mo etching solution is difficult to control within a relatively stable range, when the etching solution concentration is too high, the edge routing will be side-etched, i.e., over-etched, which may cause edge routing disconnection in severe cases; when the etching solution concentration is too low, the edge routing will be not etched cleanly, which may cause edge routing connection in severe cases. The present invention uses a printed silver paste process, without etching, only baking and laser, to obtain the required edge routing, which can solve the above problems of side etching, disconnection, unclean etching, and connection.

[0028] Beneficial effects of the present invention:

[0029] The glass sensor preparation method of the present invention protects the glass surface B while etching the glass surface A, and protects the glass surface A while etching the glass surface B, effectively preventing the glass sensor from having poor appearance such as scratches and foreign matter during the manufacturing process, and improving the appearance yield from 80% to 90%. Simultaneously, the conventional Mo-Al-Mo conductive material is replaced with a silver paste conductive material, the edge routing yellow light process is cancelled, and etching is not required, solving functional problems such as broken wires and incomplete etching, and improving the electrical yield from 90% to 95%, reducing the manufacturing process steps, reducing the loss of manpower and material resources, and reducing production costs. The appearance yield of the glass sensor prepared by this method is improved from 80% to 90%, the electrical yield is improved from 90% to 95%, the manufacturing process steps are reduced, and the production cost is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The specific implementation of the present invention will be further explained below in conjunction with the accompanying drawings.

[0031] Figure 1 This is a schematic diagram of the glass sensor structure prepared by the present invention;

[0032] Figure 2 This is a curve diagram showing the relationship between ITO thickness and ITO square resistance. DETAILED DESCRIPTION

[0033] The glass sensor preparation method of this embodiment includes the following steps:

[0034] Step S1: Use a weak alkaline or neutral cleaning agent to clean the front and back of the glass 4;

[0035] Step S2: coating ITO on the front and back of the glass 4 by magnetron sputtering, and controlling the thickness of the ITO coating by adjusting the magnetron sputtering conditions to obtain an ITO glass with a desired square resistance;

[0036] Step S3: coating photoresist on the A surface of the ITO glass, and then baking at 60° C. to 120° C. for 10 min to 30 min;

[0037] Step S4: Expose the ITO glass coated with photoresist in the designed A-surface glass mask precision exposure machine, develop it in a developer prepared with 90% solid electronic grade KOH to develop the pattern in the A-surface, and then wash it with water and air dry it to dry the liquid on the surface of the ITO glass;

[0038] Step S5: turning over the ITO glass, coating the entire surface of the B surface of the ITO glass with a photoresist of 1 μm to 5 μm, and baking at 60° C. to 120° C. for 10 min to 30 min to form a photoresist film, thereby protecting the ITO on the B surface;

[0039] Step S6: Place the A surface of the ITO glass in an etching solution for etching, remove the ITO that is not needed for the pattern in the surface, and leave the ITO that is needed for the pattern in the surface. Since the B surface is protected by the photoresist, the ITO on the B surface will not be affected when the A surface is etched. After washing with water and air drying, the photoresist is stripped and removed in a stripping solution prepared with 99% electronic grade NaOH. After washing with water and air drying, the ITO glass with the pattern 2 above is obtained.

[0040] Step S7: coating photoresist on the ITO glass surface B, and then baking at 60° C. to 120° C. for 10 min to 30 min;

[0041] Step S8: Expose the ITO glass coated with photoresist in the designed B-side glass mask precision exposure machine, develop it in a developer prepared with 90% solid electronic grade KOH to develop the pattern in the B-side, and then dry the liquid on the surface of the ITO glass after washing with water and air drying;

[0042] Step S9: turning over the ITO glass, coating the entire surface of the A surface of the ITO glass with a photoresist of 1 μm to 5 μm, and baking at 60° C. to 120° C. for 10 min to 30 min to form a photoresist film, thereby protecting the ITO on the A surface;

[0043] Step S10: Place the B surface of the ITO glass in an etching solution for etching, remove the ITO that is not needed for the pattern in the surface, and leave the ITO that is needed for the pattern in the surface. Since the A surface is protected by the photoresist, the ITO Pattern on the A surface will not be affected when the B surface is etched. After washing with water and air drying, the photoresist is stripped and removed in a stripping solution prepared with 99% electronic grade NaOH. After washing with water and air drying, the ITO glass with the following pattern 5 is obtained;

[0044] Step S11: Printing a peelable adhesive on the surface of the ITO pattern on the A side by screen printing technology, and baking it at 120° C. to 150° C. for 10 min to 30 min to form an upper peelable adhesive 1 with viscosity; then printing a peelable adhesive on the surface of the ITO pattern on the B side by screen printing technology, and baking it at 120° C. to 150° C. for 10 min to 30 min to form a lower peelable adhesive 7 with viscosity;

[0045] Step S12: printing silver paste on the edge of the ITO pattern on the A side by screen printing technology, baking at 120°C to 140°C for 10min to 30min to form a block silver paste with thickness, and then lasering a circuit with line width and line spacing by a high-precision laser machine to obtain the upper edge routing 3; then printing silver paste on the edge of the ITO Pattern on the B side by screen printing technology, baking at 120°C to 140°C for 10min to 30min to form a block silver paste with thickness, and then lasering a circuit with line width and line spacing by a high-precision laser machine to obtain the lower edge routing 6;

[0046] Step S13: Print the peelable glue on the A side by screen printing technology, and bake it at 120℃~150℃ for 10min~30min to form a thick upper peelable glue 1; then print the peelable glue on the B side by screen printing technology, and bake it at 120℃~150℃ for 10min~30min to form a thick lower peelable glue 7.

[0047] In this embodiment, the glass 4 preferably uses strengthened sodium-lime glass or aluminosilicate glass, with a strengthening stress of more than 400 MPa, a strengthening depth of 8 to 15 μm, and a glass thickness of 0.2 mm to 1.1 mm. The strengthening stress of Asahi Glass sodium-lime glass is between 400 MPa and 650 MPa, and the strengthening stress of aluminosilicate glass of Longwei, Corning, etc. is more than 700 MPa.

[0048] In this embodiment, preferably, in step S2, the ITO coating thickness is 20nm to 60nm, and the square resistance is 30Ω / □ to 100Ω / □. The thicker the ITO thickness, the lower the ITO square resistance. The relationship curve between ITO thickness and ITO square resistance is as shown in FIG. Figure 2 As shown, when the ITO thickness is 20nm, the ITO square resistance is 100Ω; when the ITO thickness is 30nm, the ITO square resistance is 60Ω; when the ITO thickness is 60nm, the ITO square resistance is 30Ω.

[0049] Preferably, in the present embodiment, in the steps S3 and S7, the coating thickness of the photoresist is 1 μm to 5 μm.

[0050] In this embodiment, preferably, the etching solution in step S6 and step S10 is aqua regia or FeCl3 prepared by 36% electronic grade HCl and 5% to 68% electronic grade HNO3.

[0051] Preferably, in this embodiment, the thickness of the silver paste in step S12 is 5 μm to 9 μm, and the line width and line spacing are 10 μm / 10 μm to 40 μm / 40 μm.

[0052] In this embodiment, the thickness of the upper peelable adhesive 1 and the lower peelable adhesive 7 in step S13 is 50 μm. The upper peelable adhesive 1 and the lower peelable adhesive 7 are a single-component solvent-based viscous liquid with good adhesive properties and mechanical properties, and can play the role of water resistance, oil resistance, acid resistance, alkali resistance, corrosion resistance, etc. After curing, a peelable film is formed. The color can be black or blue.

[0053] like Figure 1 As shown, the present embodiment also provides a glass sensor, which is manufactured through the above process, including a peelable adhesive 1, an upper inner pattern 2, an upper edge routing 3, a glass 4, a lower inner pattern 5, a lower edge routing 6 and a lower peelable adhesive 7. The upper edge routing 3 and the lower edge routing 6 are silver paste block routings printed on the edge of the in-plane pattern using CCD precision screen printing technology. After the silver paste is baked and solidified, the silver paste circuit is laser-projected by a CCD precision laser machine. The silver paste circuit is connected to the in-plane pattern channel. The upper inner pattern 2 and the upper edge routing 3 constitute a capacitive sensing layer, and the lower inner pattern 5 and the lower edge routing 6 constitute a capacitive driving layer. The capacitive sensing layer and the capacitive driving layer complete the function of signal reception and transmission.

[0054] In this embodiment, the main component of the strippable adhesive is polyvinyl chloride or a vinyl resin derivative, and the main component of the photoresist is a photosensitive resin such as propylene glycol methyl ether acetate, including components such as solvents, resins, photoinitiators and additives.

[0055] The upper inner pattern 2 and the lower inner pattern 5 are a layer of patterned ITO coated on the front and back sides of the glass 4. A layer of ITO is first coated on the glass surface by magnetron sputtering, and then the required ITO pattern is obtained by exposure, development, and etching. The pattern of the ITO pattern can be a diamond, a rectangle, a square, or other regular shapes.

[0056] Conventional glass sensors use Mo-Al-Mo as the conductive material for edge routing, and the minimum line width and line spacing is only 20um / 20um. Since the concentration of Mo-Al-Mo etching solution is difficult to control within a relatively stable range, when the etching solution concentration is too high, the edge routing will be side-etched, i.e., over-etched, which may cause edge routing disconnection in severe cases; when the etching solution concentration is too low, the edge routing will be not etched cleanly, which may cause edge routing connection in severe cases. The present invention uses a printed silver paste process, without etching, only baking and laser, to obtain the required edge routing, which can solve the above problems of side etching, disconnection, unclean etching, and connection.

[0057] The glass sensor preparation method of this embodiment protects the glass surface B while etching the glass surface A, and protects the glass surface A while etching the glass surface B, effectively preventing the glass sensor from having scratches, foreign matter and other poor appearance during the manufacturing process, and the appearance yield rate is increased from 80% to 90%. At the same time, the conventional Mo-Al-Mo conductive material is replaced with a silver paste conductive material, the edge routing yellow light process is cancelled, and no etching is required, solving functional problems such as broken wires and incomplete etching, and the electrical yield rate is increased from 90% to 95%, reducing the process steps, reducing the loss of manpower and material resources, and reducing production costs. The appearance yield rate of the glass sensor prepared by this method is increased from 80% to 90%, and the electrical yield rate is increased from 90% to 95%, the process steps are reduced, and the production cost is reduced.

[0058] Many specific details are described in the above description to facilitate a full understanding of the present invention. However, the above description is only a preferred embodiment of the present invention. The present invention can be implemented in many other ways different from those described herein, so the present invention is not limited to the specific implementation disclosed above. At the same time, any person familiar with the art can make many possible changes and modifications to the technical solution of the present invention using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a glass sensor, characterized in that: The steps include: Step S1: using a weak alkaline or neutral cleaning agent to clean the front and back of the glass (4); Step S2: coating ITO on the front and back sides of the glass (4) by magnetron sputtering, and controlling the thickness of the ITO coating by adjusting the magnetron sputtering conditions to obtain an ITO glass with a desired square resistance; Step S3: coating photoresist on the A surface of the ITO glass, and then baking at 60°C to 120°C for 10 min to 30 min; Step S4: placing the designed A-side glass in a photomask precision exposure machine, exposing the ITO glass coated with photoresist, developing it in a developer prepared with 90% solid electronic grade KOH to develop the pattern in the A-side, and then washing and air-drying to dry the liquid on the surface of the ITO glass; Step S5: turning over the ITO glass, coating the entire surface of the B surface of the ITO glass with a photoresist of 1 μm to 5 μm, and baking at 60° C. to 120° C. for 10 min to 30 min to form a photoresist film, thereby protecting the ITO on the B surface; Step S6: Place the A surface of the ITO glass in an etching solution for etching, remove the ITO not required for the in-plane pattern, and leave the ITO required for the in-plane pattern. After washing with water and air drying, remove the photoresist in a stripping solution prepared with 99% electronic grade NaOH. After washing with water and air drying, obtain the ITO glass with the above in-plane pattern (2). Step S7: coating photoresist on the B surface of the ITO glass, and then baking at 60°C to 120°C for 10 min to 30 min; Step S8: Expose the ITO glass coated with photoresist in the designed B-side glass mask precision exposure machine, develop it in a developer prepared with 90% solid electronic grade KOH to develop the pattern in the B-side, and then wash it with water and air dry it to dry the liquid on the surface of the ITO glass; Step S9: turning the ITO glass over, coating the entire surface of the A surface of the ITO glass with a photoresist of 1 μm to 5 μm, and baking at 60° C. to 120° C. for 10 min to 30 min to form a photoresist film, thereby protecting the ITO on the A surface; Step S10: Place the B surface of the ITO glass in an etching solution for etching, remove the ITO not required for the in-plane pattern, and leave the ITO required for the in-plane pattern. After washing with water and air drying, remove the photoresist in a stripping solution prepared with 99% electronic grade NaOH. After washing with water and air drying, obtain the ITO glass with the following in-plane pattern (5). Step S11: Printing a peelable adhesive on the surface of the ITO pattern on the A side by screen printing technology, and baking it at 120°C to 150°C for 10 min to 30 min to form an upper peelable adhesive (1) with viscosity; then printing a peelable adhesive on the surface of the ITO pattern on the B side by screen printing technology, and baking it at 120°C to 150°C for 10 min to 30 min to form a lower peelable adhesive (7) with viscosity; Step S12: printing silver paste on the edge of the ITO pattern on the A side by screen printing technology, baking at 120°C to 140°C for 10 min to 30 min to form a block of silver paste with thickness, and then lasering a circuit with line width and line spacing using a high-precision laser machine to obtain an upper edge routing (3); then printing silver paste on the edge of the ITO Pattern on the B side by screen printing technology, baking at 120°C to 140°C for 10 min to 30 min to form a block of silver paste with thickness, and then lasering a circuit with line width and line spacing using a high-precision laser machine to obtain a lower edge routing (6); Step S13: Printing a peelable adhesive on the A side by screen printing technology, and baking it at 120°C to 150°C for 10 min to 30 min to form a thick upper peelable adhesive (1); then printing a peelable adhesive on the B side by screen printing technology, and baking it at 120°C to 150°C for 10 min to 30 min to form a thick lower peelable adhesive (7).

2. The method for preparing a glass sensor according to claim 1, wherein: The glass (4) is made of strengthened sodium-lime glass or aluminosilicate glass, with a strengthening stress of more than 400 MPa, a strengthening depth of 8 to 15 μm, and a glass thickness of 0.2 mm to 1.1 mm.

3. The method for preparing a glass sensor according to claim 1, wherein: In step S2, the ITO coating thickness is 20 nm to 60 nm, and the square resistance is 30 Ω / □ to 100 Ω / □.

4. The method for preparing a glass sensor according to claim 1, wherein: In the steps S3 and S7, the coating thickness of the photoresist is 1 μm to 5 μm.

5. The method for preparing a glass sensor according to claim 1, wherein: The etching solution in step S6 and step S10 is aqua regia or FeCl3 prepared by 36% electronic grade HCl and 5% to 68% electronic grade HNO3.

6. The method for preparing a glass sensor according to claim 1, wherein: In step S12, the thickness of the silver paste is 5 μm to 9 μm, and the line width and line spacing are 10 μm / 10 μm to 40 μm / 40 μm.

7. The method for preparing a glass sensor according to claim 1, characterized in that: In step S13, the thickness of the upper peelable adhesive (1) and the lower peelable adhesive (7) is 50 μm.

8. A glass sensor, characterized in that: A glass sensor is prepared according to the method described in any one of claims 1 to 7, comprising a peelable adhesive (1), an upper inner pattern (2), an upper edge routing (3), glass (4), a lower inner pattern (5), a lower edge routing (6) and a lower peelable adhesive (7), wherein the upper edge routing (3) and the lower edge routing (6) are silver paste block routings printed on the edge of the in-plane pattern using CCD precision screen printing technology, and after the silver paste is baked and solidified, a silver paste circuit is laser-printed by a CCD precision laser machine, and the silver paste circuit is connected to the in-plane pattern channel, the upper inner pattern (2) and the upper edge routing (3) constitute a capacitive sensing layer, and the lower inner pattern (5) and the lower edge routing (6) constitute a capacitive driving layer, and the capacitive sensing layer and the capacitive driving layer complete the functions of signal reception and transmission.

Citation Information

Patent Citations

  • Touch sensor with single-layer ITO (indium tin oxide), manufacturing method of touch sensor and touch screen

    CN104391609A

  • Processing technique of replacing molybdenum aluminum molybdenum metal film layer in capacitive touch screen glass sensor

    CN106775151A